Census of Population and Housing, 1970 (United States): Public Use Samples ([Verlag nicht ermittelbar], 1984)
This data collection contains 132 Public Use Microdata Samples (PUMS) files from the 1970 Census of Population and Housing. Information is provided in these files on the housing unit, such as occupancy and vacancy status of house, tenure, value of property, commercial use, year structure was built, number of rooms, availability of plumbing facilities, sewage disposal, bathtub or shower, complete kitchen facilities, flush toilet, water, telephone, and air conditioning. Data are also provided on household characteristics such as the number of persons aged 18 years and younger in the household, the presence of roomers, boarders, or lodgers, the presence of other nonrelative and of relative other than wife or child of head of household, the number of persons per room, the rent paid for unit, and the number of persons with Spanish surnames. Other demographic variables provide information on age, race, marital status, place of birth, state of birth, Puerto Rican heritage, citizenship, education, occupation, employment status, size of family, farm earnings, and family income. This hierarchical data collection contains approximately 214 variables for the 15-percent sample, 227 variables for the 5-percent sample, and 117 variables for the neighborhood characteristics sample.